Political Socialization In The Gurukul Learning At Devghat Nepal - Sharma, Chandramani (Journal of Advanced Academic Research, 2025)
The system of education that is ranked on the basis of Hindu culture selects the methodology to be the Gurukul system because it combines Political Theories with Holistic learning and moral development. This study looked at the impact of Gurukuls in the formation of citizenship values, toleration and cultural inheritance in the region of Devghat, Nepal. The quantitative gathered through structured observations, key informant interviews and questionnaires among 36 participants in seven Gurukuls was part of a mixed-methods design. The results are a reflection of Gurukuls well-disciplined time schedules to good teaching practices and discipline. Participants heavily favored Gurukul education and its capability to address modern societal demands and culture, asserting that it can be tailored to overcome challenges of today. There was caste, ethnic and geographic representation — in which case one will say that Inclusivity has come a long way in making Education more democratic. Moreover, Gurukuls incorporate cultural traditions like Garbhadhana and Upanayana, which provide civic values and social principles encouraging the values of democracy and integrationalism. All of these, however exciting they sound; are countervailed by the challenges of contemporary pedagogic technology and risen above casting out historical exclusions reigning in Gurukuls. This is a down side because if it could be improved, the whole system would be updated/used more appropriately the study highlights the key role that education in Gurukul can play in filling up gaps but also in changing ordinary values and re molding them according to modern needs of society so as to direct democratic development with cultural heritage whereas Nepal is concerned. Conclusions: Based on the above discussion, a few suggestions are proposed, such as a general orientation toward more modern teaching techniques and greater inclusiveness of Gurukuls in educational policy-making for their sustainability and relevance, which is becoming important at a time when the world is changing at an unprecedented speed.